A novel nest‐monitoring camera system using a Raspberry Pi micro‐computer. Issue 4 (14th November 2016) - Prinz, Anna C. B.; Taank, Vikas K.; Voegeli, Vincent; Walters, Eric L.
Abstract: The utility, availability, cost‐effectiveness, and reliability of prefabricated video systems designed to monitor wildlife have lagged behind the unique and varied needs of many researchers. Many systems are limited by inflexible video settings, lack of adequate data storage, and cannot be programmed by the user. More sophisticated systems can be cost prohibitive, and the literature describing remote wildlife video monitoring has, for the most part, not incorporated advances in camera and computer technology. Here, we present details of a pilot study to design and construct a lower cost (US 340) nest camera system to record the behavior of Acorn Woodpeckers ( Melanerpes formicivorus ) in artificial tree cavity nests. This system incorporates a Raspberry Pi micro‐computer, Pi NoIR infrared camera, a wireless adapter to transmit video over the Internet, and Deka rechargeable gel batteries for power. We programmed the system to motion‐sense, to record exclusively during daylight hours, and to automatically upload videos to the cloud over wireless Internet. The Raspberry Pi micro‐computer does not require advanced programming or electrical engineering skills to build and configure and, because it is programmable, provides unprecedented flexibility for field researchers who wish to configure the system to the specific needs of their study.